2010
DOI: 10.2353/ajpath.2010.091037
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Abnormalities in Mitochondria Associated with Synaptic Degeneration in Prion Disease

Abstract: Synaptic and dendritic pathology is a well-documented component of prion disease. In common with other neurodegenerative diseases that contain an element of protein misfolding, little is known about the underlying mechanisms of synaptic degeneration. In particular, in prion disease the relationship between synaptic malfunction, degeneration, and mitochondria has been neglected. We investigated a wide range of mitochondrial parameters, including changes in mitochondrial density, inner membrane ultrastructure, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 57 publications
7
68
0
Order By: Relevance
“…Because levels of the mitochondrially localised SOD2 were decreased in chronically infected cells, mitochondrial representation within the cell was considered, but no difference was seen between the overall mock and infected populations. This lack of change is consistent with the investigations of Sisková et al, who found no prion-disease-associated changes in mitochondrial density or expression of mitochondrial proteins (Sisková et al, 2010). The same study did find changes to the mitochondrial inner membrane morphology and reduced cytochrome c oxidase activity, and similar observations were also made by others (Choi et al, 1998; Lee et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Because levels of the mitochondrially localised SOD2 were decreased in chronically infected cells, mitochondrial representation within the cell was considered, but no difference was seen between the overall mock and infected populations. This lack of change is consistent with the investigations of Sisková et al, who found no prion-disease-associated changes in mitochondrial density or expression of mitochondrial proteins (Sisková et al, 2010). The same study did find changes to the mitochondrial inner membrane morphology and reduced cytochrome c oxidase activity, and similar observations were also made by others (Choi et al, 1998; Lee et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…At high magnification, although the intravacuolar mitochondria were slightly swollen (Fig 5B, colored purple), cytoplasmic mitochondria rather maintained a functional small morphology and the cristae (Fig 5B, colored green). Mitochondrial swelling, generally reflected by an increase of the mitochondrial area is a well-accepted hallmark of dysfunction of this organelle [51,52]. Mitochondria area measurements in hepatocytes showed that the MMP significantly suppressed the increasing of mitochondria area compared to HMP (Fig 5C, HMP_4h vs. MMP_4h, 0.68±0.02 vs. 0.39±0.02 μm 2 per mitochondria, *P<0.0001).…”
Section: Resultsmentioning
confidence: 98%
“…In prion diseases, the impairment of mitochondrial function is repeatedly observed, which could potentially contribute to or even initiate the various abnormalities, for example, synaptic pathology, 24 faulty calcium metabolism, 25 high level of ROS, 26 and apoptosis of neurons. 27 However, it has still been unclear whether mtDNA mutations as a risk factor for sCJD.…”
Section: Discussionmentioning
confidence: 99%